Evaluación de las propiedades físico químicas y microbiológicas de galletas dulces enriquecidas con lactosuero. - Ñacata Oña, Elizabeth Michel (2022)
This research was carried out to generate a study of the physical, chemical, microbiological, and sensory properties of crackers. In the country is a substance that has not been investigated the properties of the sub-product from a process of cheese making where its extraction is done in an artisanal or industrialized way to be thrown or in turn serve as animal feed. The whey has similar benefits to milk if it comes true. It is a sub-product of milk. The titration work was done to verify the properties and benefits for consumers and large industries. The cookie industry is an industry with great potential worldwide and has excellent initiatives to improve or provide added value. For that reason, the experimental unit of this project is the sweet cookies to know the properties of whey used in a cookie. It is essential to verify the properties that are encompassed concerning the whey since, in the world of the industry, it is a compliment that projects and improvements can be a sub-product of quality and not a waste. The project starts with the elaboration of sweet cookies with whey through whey extraction and dough elaboration to obtain the experimental unit of the project, checking the results with physical-chemical analysis, which were: pH and humidity, microbiological: molds and yeasts, and sensory: odor, color, flavor, and texture.